2023
DOI: 10.3390/su15107971
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development and Implementation of Quality Management Excellence Models in Public Organizations: A Systematic Literature Review

Effrosyni Taraza,
Sofia Anastasiadou,
Andreas Masouras
et al.

Abstract: Purpose: The purpose of this study was to determine the effects of the European Foundation for Quality Management Excellence Model and Six Sigma and Lean Six Sigma approaches in public organizations. Design/methodology/approach: A systematic literature review was conducted based on articles from three academic publishers (Emerald, Elsevier/Science Direct and Taylor & Francis). The 88 selected journal articles were published between 2004 and 2022 and documented the results of the quality tools. Findings: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 189 publications
0
3
0
Order By: Relevance
“…The effective application of the model in the educational sector requires further research to improve the efficiency of educational systems and processes and student satisfaction [166]. The studies selected in the present research prove that, through the strengthening of continuous improvement processes, the EFQM Excellence Model enhances institutions' competitive advantages and contributes to the creation of equal preconditions of high-quality education [167,168]. The authors of [168,169] claim that a combination of the EFQM Excellence Model and statistical control tools, such as Six Sigma, Failure Modes and Effects Analysis (FMEA), and Pareto Chats statistical inference, should be used in quality assessments.…”
Section: Discussionmentioning
confidence: 63%
“…The effective application of the model in the educational sector requires further research to improve the efficiency of educational systems and processes and student satisfaction [166]. The studies selected in the present research prove that, through the strengthening of continuous improvement processes, the EFQM Excellence Model enhances institutions' competitive advantages and contributes to the creation of equal preconditions of high-quality education [167,168]. The authors of [168,169] claim that a combination of the EFQM Excellence Model and statistical control tools, such as Six Sigma, Failure Modes and Effects Analysis (FMEA), and Pareto Chats statistical inference, should be used in quality assessments.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, the study results revealed that Six Sigma is a comprehensive and structured process that adds value and helps educational institutions to achieve desired quality standards and meet customer needs. The research findings determined that the Six Sigma quality tool is a process improvement tool that educational institutions can use to dig deeper into the root causes of problems in educational processes, enabling them to be resolved, reduced or mitigated, thereby allowing schools and educational institutes to achieve the desired quality standard (Mazumder, 2014;Taraza et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, continuous improvement is needed to ensure that the quality of education meets the standards set by education policymakers. Many continuous improvement models, approaches, and tools have been implemented in educational institutions to ensure that the quality of education is improved and maintained (Taraza et al, 2023;Xin et al, 2021). Various standard improvement tools are used in educational institutions, such as Total Quality Management (TQM) (Sohel-Uz-Zaman & Anjalin, 2016;Tresnasari et al, 2020), Kaizen (Kolodziejczak et al, 2019;Susana et al, 2021), Six Sigma (Sandu & Sharma 2020;Wang 2022), Lean Six Sigma (Shanshan et al, 2022;Xin et al, 2021) and Balanced Scorecard (Camilleri, 2021;Cheowsuwan, 2016).…”
Section: Introductionmentioning
confidence: 99%